Efficacy of Silicon and potassium in the Amelioration of Iron in Rice Culture - Lakshmikanthan K (Department of Agronomy, College of Horticulture, 2000)
The study entitled "Efficacy of silicon and potassium In the amelioration of iron in rice culture" was carried out during virippu and mundakan seasons of 1999-2000 at Agricultural Research Station, Mannuthy, with the objective to evaluate the efficacy of silicon and potassium in ameliorating the stress influences of excess iron on rice productivity in laterite soils as well as to characterise their influences on growth and yield of rice. Combined application of sources and levels of silica with levels of K increased the grain yield by 1000 kg ha" over control. Among the three sources of silica sodium silicate recorded the highest grain yield of 6644 kg ha" followed by fine silica (6282 kg ha') and rice husk (6113 kg ha'). Increasing the level of K application to 52.5 and 70 kg ha", as against the package of practices recommendation of 35 kg K ha', increased the grain yield by 951 and 1125 kg ha', respectively. The yield of straw significantly varied among the sources and levels of silica and levels of K and sodium silicate recorded the highest yield of 4128 kg ha". Content and uptake of Fe showed a decreasing trend from panicle initiation to flowering stage where as an increasing trend was noted in respect of Si02 due to the general treatment effect. Three factor interaction effect showed that the treatment receivmg 500 kg Si ha" as sodium silicate in combination with 70 kg K ha" recorded the highest yield 0[7306 kg ha" and it also recorded reduced contents of Fe and Mn at panicle initiation and Fe attlowering. During rabi season the residual effect of general treatments increased the grain yield by 571 and 358 kg ha' in the absence and presence of applied potash.